INNOVATIVE ACTIVITY OF TEACHERS AT GENERAL SECONDARY SCHOOL - Ruzmetova Khilola Abdushoripovna (Galaxy International Interdisciplinary Research Journal, 2024)
The modernization of the educational system of continuing education in Uzbekistan is closely related to the innovative activities of teachers and lecturers. In pedagogical science, innovative activity is understood as purposeful pedagogical activity, based on understanding one’s own pedagogical experience through comparison and study, change and development of the teaching and educational process in order to achieve better results, obtain new knowledge, and introduce qualitatively different pedagogical practices [1, p. . 58].